A one-step method to fabricate novel three-dimensional GaP nanopore arrays for enhanced photoelectrochemical hydrogen production. Issue 91 (3rd November 2017) - Liu, Pengjie; Zheng, Maojun; Li, Qiang; Ma, Liguo; Wang, Faze; Jiang, Dongkai; Song, Jingnan; You, Yuxiu; Ma, Li; Shen, Wenzhong
Abstract : We present a facile one-step method to fabricate GaP nanopore arrays with novel 3D interior architectures for enhanced photoelectrochemical hydrogen production. Abstract : Gallium phosphide nanopore arrays with unique three-dimensional interior architectures (3D GaP NPs) are fabricated by electrochemical etching in a neutral solution. As the photoanodes for photoelectrochemical (PEC) hydrogen production, the 3D GaP NPs exhibited a larger photocurrent density (5.65 mA cm −2 at 0 V vs. RHE, which is 58.3 and 2.3 times as large as that of the planar wafer and the NPs reported by our group in our previous work respectively) and a lower onset potential (−0.58 V vs. RHE, shifting negatively nearly 300 mV compared with its counterparts in the previous work). Besides the excellent light-trapping characteristics of the nanostructures, electrochemical impedance spectroscopy (EIS) further confirmed that the enhanced PEC performance was ascribed to the more efficient charge separation and transfer, and the increased surface area with the unique 3D NP arrays. Furthermore, the efficient charge separation may be attributed to the passivated surface states by the neutral solution.